The basics of investigating forensic science : a laboratory manual - Mirakovits, Kathy; Londino-Smolar, Gina (Boca Raton : CRC Press, Taylor & Francis Group, 2021)
"Designed to provide hands-on practicums for students to learn foundational concepts in forensic science, The Basics of Investigating Forensic Science, Second Edition presents laboratory techniques through engaging exercises. It is a perfect text offering engaging lab projects on a range of subjects including fingerprinting, shoeprint analysis, firearms, pathology, anthropology, forensic biology and DNA, drugs, trace evidence and more. The book is highly illustrated with extensive photos and diagrams to illustrate processes and concepts. The book can be used alongside any textbook, and even as a stand-alone text for 2- and 4-year college programs as well as at the high school level. The edition is fully updated to include the latest advances with more diagrams of laboratory procedures including diagrams of how equipment is setup for a given exercise. The focus is on laboratory procedure, techniques, and interpretation of results. Many of the exercises can be done with minimal laboratory equipment and material while many exercises also have additional options and advanced lab exercises for educations with access to more specialized and advance lab equipment. As such, The Basics of Investigating Forensic Science, Second Edition is an excellent resource for introduction to forensic sciences courses and classroom material, including the companion textbook it was designed to accompany, Forensic Science: The Basics, soon to be available in its Fourth Edition. Sequencing of laboratory exercises is designed to follow the Basics textbook, however, the lab exercises can be done in any sequence desired by an instructor"--
Includes bibliographical references and index.
Keywords: Forensic sciences -- Laboratory manuals; Criminal investigation -- Laboratory manuals